2018
DOI: 10.1111/evo.13453
|View full text |Cite
|
Sign up to set email alerts
|

Extreme dentition does not prevent diet and tooth diversification within combtooth blennies (Ovalentaria: Blenniidae)

Abstract: The dentition of fishes can be quite striking and is often correlated with a specific diet. Combtooth blennies have long incisiform oral teeth, unlike most actinopterygians. It has been suggested that the long tooth morphology is an adaptation for detritivory, but given the diversity of diets (detritus, coral polyps, polychaetes, and pieces of other fishes), are blenny teeth indeed monomorphic? Or does tooth variation associated with diet still exist at this extreme? To explore tooth and diet diversification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 49 publications
(119 reference statements)
4
24
2
Order By: Relevance
“…This molecular phylogeny confirmed the monophyly of the genus Scartichthys. Molecular evidence (Hundt et al, 2014;Hundt & Simons, 2018) confirmed that Scartichthys was sister to Ophioblennius as formerly hypothesized by Williams (1990) using morphological data. Interestingly, a minimal divergence between S. crapulatus and S. viridis was retrieved, questioning whether this divergence was of the order of inter or intraspecific divergence and paralleling the concern expressed by Stepien (1990) regarding the validity of S. crapulatus.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This molecular phylogeny confirmed the monophyly of the genus Scartichthys. Molecular evidence (Hundt et al, 2014;Hundt & Simons, 2018) confirmed that Scartichthys was sister to Ophioblennius as formerly hypothesized by Williams (1990) using morphological data. Interestingly, a minimal divergence between S. crapulatus and S. viridis was retrieved, questioning whether this divergence was of the order of inter or intraspecific divergence and paralleling the concern expressed by Stepien (1990) regarding the validity of S. crapulatus.…”
Section: Introductionsupporting
confidence: 73%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 22, 2021. ; https://doi.org/10.1101/2021.02.22.432327 doi: bioRxiv preprint 6 Finally, the recent phylogeny of blenniids (Hundt & Simons, 2018) represents the first attempts to reconstruct the evolutionary history of Scartichthys including one representative of the four currently valid species based on five nuclear markers (refer to Supplementary Figure S1 in Hundt & Simons (2018)). This molecular phylogeny confirmed the monophyly of the genus Scartichthys.…”
Section: Introductionmentioning
confidence: 99%
“…This action is enacted by fishes that specialize in scraping algae or detritus off rocks and possess similar stockade‐like dentitions (Parenti and Maciolek ; Streelman and Albertson ; Bellwood et al. ; Hundt and Simons ). Freshwater stream gobies of the Stenogobius group (formerly subfamily Sicydiinae; Thacker and Roje ; Agorreta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, cleaning involves the dislodging of firmly attached objects from a substratum. This action is enacted by fishes that specialize in scraping algae or detritus off rocks and possess similar stockade-like dentitions (Parenti and Maciolek 1993;Streelman and Albertson 2006;Bellwood et al 2014;Hundt and Simons 2018). Freshwater stream gobies of the Stenogobius group (formerly subfamily Sicydiinae; Thacker and Roje 2011;Agorreta et al 2013) are exemplar analogs to dedicated cleaners due to their tightly packed rows of elongate teeth and inferior mouths (Parenti and Maciolek 1993).…”
Section: Morphology Of Cleaner Gobiesmentioning
confidence: 99%
“…Combtooth blennies are small (< 10 cm) scaleless fish that 94 are commonly found in many shallow tropical and warm water marine habitats, including 95 coral reefs, estuaries, mangroves, tide pools, and sometimes on land (Hundt et al 2014a, 96 Hundt and Simons 2018). They comprise one of the most diverse percomorph families 97 consisting of 400 described species (58 genera; fishbase.org) that fall into 13 phylogenetic 98 clades (Hundt et al 2014a, Hundt andSimons 2018). Within the Salariini division of 99 blennies, amphibious behaviour is common, and more than twenty species in at least three 100 genera exhibit a highly terrestrial lifestyle (Ord and Cooke 2016).…”
Section: Introduction 35mentioning
confidence: 99%